The role of extracellular volume fraction in predicting left ventricular reverse remodelling and adverse outcomes in patients with non-ischemic cardiomyopathy and reduced left ventricular ejection fraction - Hwei Sung, Ling; en ze, Chan; Han Bing, Chow (Elsevier, 2023)
Cardiac magnetic resonance (CMR) permits the quantification of extracellular volume fraction (ECV) which is a surrogate marker of myocardial interstitial fibrosis. ECV has been shown to predict heart failure (HF) events. Conversely, left ventricular reverse remodelling (LVRR) defined as decrease in chamber volumes and improvement in function, has a positive impact on prognosis. In patients with non-ischemic cardiomyopathy (NICM), the role of ECV in LVRR is not established. Purpose To study the association between ECV and LVRR events in patients with NICM with reduced left ventricular ejection fraction (LVEF). Method Consecutive patients with NICM with LVEF ≤40% who underwent CMR between 2016 and 2021 in Sarawak Heart Center and had ECV quantification were included. Patients with late gadolinium enhancement suggesting infarctions were excluded. The cohort was stratified into ECV ≤ 29% (upper limit of normal) and >29%. The index and 1-year echocardiographic parameters relating to LVRR [LVEF, LV end-systolic volume index (LVESVi) and LV end-diastolic volume index (LVEDVi)] were analysed for associations with Results 63 patients were included for analysis. 66% had ECV >29%. Baseline characteristics, symptom severity and intensity of guideline-directed medical therapy (GDMT) for HF were similar in both groups. Those with ECV >29% had worse LVEF, LVEDVi and LVESVi at index echocardiography. At follow up echocardiography, both ECV groups had improvements in these parameters with no statistical difference between the groups. There were more patients in the ECV >29% with LVEF improving ≥10% to >40% (50% versus Conclusion In our cohort of NICM patients with reduced LVEF and exposed to GDMT for HF, LVRR was observed regardless of ECV. However, ECV >29% was associated with worse parameters of adverse LV remodelling at index echocardiography, all-cause mortality and HF events. ECV may confer additional value in the prognostication of HF patients beyond LVRR.